The impact of Income Diversification on Performance and Risk Taking: Case in Indonesia’s Shariah Banking during covid-19 - Indra Maulana; Estu Widarwati; Nunik Nurmalasari; E Wityasminigsih (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2023)
The banking development is increasingly rapid and competition is an important aspect for maintaining the existence of a bank that can achieved by income optimalizing and minimazing of risk taking. This study examines the effect of income diversification on sharia bank’s performance, and also aims to test the effect of income diversification on performance and risk taking. The sharia bank’s performance proxied by return on equity and measurement of risk-taking using z-score. The samples are sharia banks registered in the financial services authority during 2019-2020. We use the descriptive statistic analysis and panel data regression processed by eviews 9. We found that income diversification not effect on both of performance and risk taking. During covid, sharia bank tends to have lower income diversification as same as lower performance, but having higher risk taking.